Researching Social Movements: Methodological Choice - Harutyunyan, Gayane (Journal of Sociology: Bulletin of Yerevan University, 2022)
In the second half of the 19th century, the world was confronted with large-scale social movements, which changed the relations between the citizen and the state once and for all. Particularly, the emergence of the Suffragette movement, then Vietnam’s anti-war movement, as well as the influence of many other smaller, local, short-term social movements, raised new questions for the scientific community. How to study social movements? Which method is more convenient and how to apply it? What kind of knowledge can be developed by studying social movements, how can society benefit from that knowledge? There are many answers to these questions, which are contradictory even today.This article is an attempt to present the features of the main sociological methods of studying social movements, which play a key role in the exploration of the phenomenon. The article discusses the peculiarities of such research methods as observation, case study, grounded theory, survey and analysis of documents from the perspective of studying social movements.
Keywords: social movement; methodology; method; observation; case study; grounded theory; document analysis; survey; triangulation